Saridinn dalam Perguluman Islam dan Tradisi: Relevansi "Islamisme" Saridin Bagi Pendidikan Karakter Masyrakat Pesisir - Nur Said (Hikmah: Journal of Islamic Studies, 2011)
Saridin’s popularity in the grassroots of the community is not only because of the strange attitudes and behavior in the era of kuwalen (Walisongo) especially when struggling and interacting with Sunan Kudus. Saridin left many teachings that are still inherent in the local community in Pati. Saridin’s existence with all existing images seems to have helped in constructing this public awareness, even in a particular group, it participates in constructing pattern of beliefs and value system that embodied in the “Religion of the People.” Story, legend and history of Saridin in the coastal community remain strong in the grassroots of the community because the cultural reproduction process is still ongoing whether through art, literature or local tradition. In connection with its relation with Islam, Saridin’s images and traditions can be identified at least into two: Firstly, in a struggle with tradition, Saridin is known by the innocence and spirit out of order (status quo) through a resistance with an attitude of “nggendeng” ie, pretending not to know, to know as it is shown through attitudes and behaviors of the community of Sedulur Sikep (sikepisme) in Sukolilo, Pati. Secondly, in a struggle within Islam, Saridin has created a kind of variant of sufistic-populist Islam namely Islam that is simple with attitudes and kasunyatan that are not rigid. Keywords: struggle, folk religion, local tradition. Kepopuleran Saridin dalam masyarakat bawah (grass root) bukan saja karena berbagai keanehan sikap dan perilakunya di zaman kuwalen ( walisongo) terutama ketika bergumul dan berinteraksi dengan Sunan Kudus. Saridin juga meninggalkan berbagai ajaran yang masih melekat dalam masyarakat lokal di Pati. Eksistensi Saridin dengan segala pencitraan yang ada ini agaknya telah turut mengkonstruksi kesadaran masyarakat, bahkan pada kelompok tertentu turut mengkonstitusi pola keyakinan dan sistem nilai sehingga terwujud dalam “ Agama Rakyat.” Cerita, kisah, legenda dan sejarah Saridin dalam mesyarakat pesisir masih bertahan kuat di masyarakat bawah karena proses reproduksi budaya masih terus berlangsung baik melalui seni, karya sastra maupun tradisi lokal. Berkaitan dengan persentuhannya dengan Islam, citra dan tradisi Saridin setidaknya dapat diidentifikasi menjadi dua; Pertama dalam bergumul dengan tradisi, Saridin dikenal dengan keluguan dan semangat keluar dari tatanan (status quo) melalui perlawanan dengan sikap “nggendeng” yakni berlagak tidak tahu, untuk tahu sebagaimana terejawantahkan dalam sikap dan perilaku komunitas Sedulur Sikep ( sikepisme) di Sukolilo, Pati. Kedua, Saridin dalam bergumul dalam Islam telah memunculkan semacam varian Islam sufistik-populis, yakni warna Islam yang sederhana dengan perilaku dan kasunyatan, tidak terlalu baku. Kata Kunci: pergumulan, agama rakyat, tradisi lokal